Abdominal vagus nerve stimulation alleviates collagen-induced arthritis in rats - Payne, Sophie C.; Romas, Evange; Hyakumura, Tomoko; Muntz, Fenella; Fallon, James B. (Frontiers in Neuroscience, 2022)
Rheumatoid arthritis (RA) is a chronic, autoimmune inflammatory disease. Despite therapeutic advances, a significant proportion of RA patients are resistant to pharmacological treatment. Stimulation of the cervical vagus nerve is a promising alternative bioelectric neuromodulation therapeutic approach. However, recent clinical trials show cervical vagus nerve stimulation (VNS) was not effective in a significant proportion of drug resistant RA patients. Here we aim to assess if abdominal vagus nerve stimulation reduces disease severity in a collagen-induced arthritis (CIA) rat model. The abdominal vagus nerve of female Dark Agouti rats was implanted and CIA induced using collagen type II injection. VNS (1.6 mA, 200 μs pulse width, 50 μs interphase gap, 27 Hz frequency) was applied to awake freely moving rats for 3 h/day (days 11–17). At 17 days following the collagen injection, unstimulated CIA rats (n = 8) had significantly worse disease activity index, tumor necrosis factor-alpha (TNF-α) and receptor activator of NFκB ligand (RANKL) levels, synovitis and cartilage damage than normal rats (n = 8, Kruskal–Wallis: P < 0.05). However, stimulated CIA rats (n = 5–6) had significantly decreased inflammatory scores and ankle swelling (Kruskal–Wallis: P < 0.05) compared to unstimulated CIA rats (n = 8). Levels of tumor necrosis factor-alpha (TNF-α) remained at undetectable levels in stimulated CIA rats while levels of receptor activator of NFκB ligand (RANKL) were significantly less in stimulated CIA rats compared to unstimulated CIA rats (P < 0.05). Histopathological score of inflammation and cartilage loss in stimulated CIA rats were no different from that of normal (P > 0.05). In conclusion, abdominal VNS alleviates CIA and could be a promising therapy for patients with RA.